2014
DOI: 10.4254/wjh.v6.i2.98
|View full text |Cite
|
Sign up to set email alerts
|

Methylsulfonylmethane suppresses hepatic tumor development through activation of apoptosis

Abstract: AIM:To investigate the effect of methylsulfonylmethane (MSM), recently reported to have anti-cancer effects, in liver cancer cells and transgenic mice. METHODS:Three liver cancer cell lines, HepG2, Huh7-Mock and Huh7-H-ras G12V , were used. Cell growth was measured by Cell Counting Kit-8 and soft agar assay. Western blot analysis was used to detect caspases, poly (ADP-ribose) polymerase (PARP), and B-cell lymphoma 2 (Bcl-2) expressions. For in vivo study, we administered MSM to H-ras 12V transgenic mice for 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Moreover, the hyperactivation of the MEK/ERK and PI3K/AKT/mTOR signaling pathways was a marked molecular event in HCC . Reports based on the Ras‐Tg mouse demonstrate that it is a valuable model to investigate molecular mechanisms, diagnosis and therapeutic strategies, and biomarkers of hepatocarcinogenesis . For example, by exploring Ras‐Tg mice, we found that differences in the molecular responses to the deregulated Ras oncoprotein between females and males determine the onset of HCC, which may contribute to the striking male prevalence of HCC .…”
Section: Introductionmentioning
confidence: 89%
“…Moreover, the hyperactivation of the MEK/ERK and PI3K/AKT/mTOR signaling pathways was a marked molecular event in HCC . Reports based on the Ras‐Tg mouse demonstrate that it is a valuable model to investigate molecular mechanisms, diagnosis and therapeutic strategies, and biomarkers of hepatocarcinogenesis . For example, by exploring Ras‐Tg mice, we found that differences in the molecular responses to the deregulated Ras oncoprotein between females and males determine the onset of HCC, which may contribute to the striking male prevalence of HCC .…”
Section: Introductionmentioning
confidence: 89%
“…33) A recent report suggested that sertraline induces apoptosis in HepG2 cells through the MAPK pathway. 15) Based on these reports, it is suggested that apoptosis through activation of the caspase pathway is involved in sertraline-induced toxicity in HepG2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…This micronutrient is well tolerated for arthritis and a number of other conditions related to inflammation, physical function, and performance. Emerging research suggests that MSM may one day aid in the treatment of various types of cancer [49,99,100,101,119,120,121,122,123,125,126,181,184,185,186,194] or metabolic syndromes [195]. …”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies indicate that MSM can induce apoptosis in gastrointestinal cancer cells [119], hepatic cancer cells [120], and colon cancer cells [121]. Contrary to these findings, MSM did not induce apoptosis in murine breast cancer cells [122].…”
Section: Mechanisms Of Actionsmentioning
confidence: 99%
See 1 more Smart Citation